Magic and other misdemeanors - Buckley, Michael, 1969- (Buckley, Michael, 1969- Sisters Grimm, 2008)
Fairy-tale detectives Sabrina and Daphne Grimm try to find out who is stealing the magical possessions of the most powerful Everafters in town.